2005
DOI: 10.1094/pd-89-0675
|View full text |Cite
|
Sign up to set email alerts
|

Epidemics of Soybean Rust (Phakopsora pachyrhizi) in Brazil and Paraguay from 2001 to 2003

Abstract: In 5 March 2001, a severe rust outbreak was recorded at Pitapó, Paraguay, and the causal organism was determined to be Phakopsora pachyrhizi using polymerase chain reaction (PCR) and DNA sequence analysis. In May, rust surveys showed spread throughout most of Paraguay and into western and northern Parana, Brazil. In the 2001-02 season, rust was widespread in Paraguay, but losses were reduced due to severe drought; however, in Brazil it spread to more than 60% of the soybean acreage, causing field losses estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
223
0
81

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(304 citation statements)
references
References 2 publications
0
223
0
81
Order By: Relevance
“…), relatada pela primeira vez no Brasil em 2001. Desde a safra agrícola de 2003/2004, essa doença tem sido constatada em todas as regiões produtoras de soja no país, exceto em Roraima, causando perdas da ordem de 10% a 90% (YORINORI et al, 2005).…”
Section: Introductionunclassified
“…), relatada pela primeira vez no Brasil em 2001. Desde a safra agrícola de 2003/2004, essa doença tem sido constatada em todas as regiões produtoras de soja no país, exceto em Roraima, causando perdas da ordem de 10% a 90% (YORINORI et al, 2005).…”
Section: Introductionunclassified
“…(Conab, 2011). Apesar de a produtividade de soja no Paraná estar acima da média nacional (3360 kg ha -1 ), a ferrugem asiática, causada por Phakopsora pachyrhizi Sydow, causa perdas elevadas de produção, podendo variar de 10 a 90% Yorinori et al, 2005).…”
Section: Introductionunclassified
“…SBR was Wrst identiWed in Japan in 1902 (Hennings 1903), Hawaii in 1994 (Killgore and Heu 1994), and Brazil in 2001 (Yorinori et al 2005). After SBR was Wrst discovered in the continental USA in plots at the Louisiana State University research station in 2004 (Schneider et al 2005), the disease spread to 20 US states, to Ontario in Canada, and to 9 states in Mexico (Isard et al 2005;Hershman et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Soybean yield losses up to 80 % in experimental trials have been reported in Asia (Hartman et al 1991) and 63 % have been reported in Brazil during 2003, 60 % in Paraguay during 2001 (Yorinori et al 2005), up to 100 % in South Africa (Caldwell and McLaren 2004), and up to 55 % in the USA (Mueller et al 2009). Because commercial soybean cultivars resistant to SBR are not available in the USA, fungicide applications are the only method currently available to control the disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation